Pengaruh Penggunaan Model Pembelajaran Word Square terhadap Hasil Belajar IPS di Sekolah Dasar - Nila Putri; Victor Novianto (UM Purwokerto Press, 2022)
The selection of learning models used by teachers in learning activities is one of the determining factors for the success of student learning. This study aims to determine the effect of the Word Square learning model on social studies learning outcomes. This research was conducted at SD Negeri Bintaos, Tepus, Gunungkidul Regency. The research subjects were students of class VI SD Negeri Bintaos with a total of 20 students consisting of 9 male students and 11 female students. This research is a Quasi Experiment, using the Control Group Pretest and Posttest design. Data was collected by using test results in the form of pretest and posttest to determine students' social studies learning outcomes. The results showed that the difference in the average value in the experimental group and the control group. The average value of the experimental group was 82.70 while the average value of the control group was 74.70. The results of the calculation of the t test, sig. (2-tailed) 0.031 <0.05 which indicates that Ho is rejected, meaning that there is a significant difference between the experimental group and the control group. Based on the results of the analysis, it can be said that the Word Square learning model has an effect on social studies learning outcomes.